(untitled) (Bangladesh Journal of Physiology and Pharmacology, 2015)
A cross-sectional descriptive study was carried out among individuals attending the ENT out-patient department from 1st June 2012 to 3Oth August 2012 in Z.H. Sikder Womens Medical College & Hospital, Dhaka. Bangladesh. The primary aim of this study was to generate up to date information on drug use in the ENT outpatient service of our hospital indications for use. A total of 150 prescriptions were randomly audited at varying time interval from the department of ENT during a three month period. The data was collected in customized proforma. Maximum cases were of otitis media 74(49.33%), sinusitis 24 (16.00%), tonsilitis 15 (10.00%), pharyngitis 14 (09.33%), DNS 14 (09.33%), rhinitis 07 (04.66%), adenoiditis 02 (01.33%). The average number of drugs used in the prescriptions was 2.94%. None of the drugs were prescribed by generic name. All of them were prescribed with trade names. The topical preparations were the most commonly prescribed drugs. Middle and lower income group of patients generally attend out-patient department, the average cost per prescription was 112 taka. The average cost to be high in this group. Educational sessions for the doctors at different levels to encourage prescribing by generic names and on correct writing of prescriptions may be considered. Studies covering a larger number of patients and for a longer time period are required. A greater number of patients can be studied, seasonal variations can be overcome and drug utilization can be measured quantitatively. DOI: http://dx.doi.org/10.3329/bjpp.v30i2.22682 Bangladesh J Physiol Pharmacol 2014; 30(2): 41-45